Experimental seismic performance of a full-scale unreinforced clay-masonry building with flexible timber diaphragms. (15th April 2018) - Kallioras, Stylianos; Guerrini, Gabriele; Tomassetti, Umberto; Marchesi, Beatrice; Penna, Andrea; Graziotti, Francesco; Magenes, Guido
Highlights: Full-scale shake-table test on a clay URM building specimen with flexible diaphragms. Detailed information about geometry and mechanical properties. Input motions selected to be compatible with gas-field induced seismicity hazard. Damage mechanisms evolution, limit states, hysteretic and dynamic response. Full data available atwww.eucentre.it/nam-project . Abstract: This paper presents the results of a unidirectional shake-table test performed on a full-scale, single-storey unreinforced masonry building. The specimen represented a typical detached house of the Groningen region of the Netherlands, consisting of double-wythe clay-brick unreinforced masonry walls, without any specific seismic detailing. The building prototype included large openings and a reentrant corner, causing a discontinuity in one of the perimeter walls. The floor was made of timber beams and planks, resulting in a flexible diaphragm. The roof, characterized by a very steep pitch, consisted of a series of timber trusses connected by wood purlins and boards. The two façades perpendicular to the shaking direction were designed to represent two typical gable geometries. An incremental dynamic test was conducted up to the near-collapse state of the specimen, using input ground motions compatible with induced-seismicity scenarios for the examined region. This paper summarizes the main characteristics of the specimen and the shake-table experimental results, illustrating the dynamic response of the structure, the evolution of the damage mechanisms, and the attainment of significant limit states.